Disease‐causing mutations in the promoter and enhancer of the ornithine transcarbamylase gene - Jang, Yoon J.; LaBella, Abigail L.; Feeney, Timothy P.; Braverman, Nancy; Tuchman, Mendel; Morizono, Hiroki; Ah Mew, Nicholas; Caldovic, Ljubica (Human mutation, 2018)
The ornithine transcarbamylase (OTC) gene is on the X chromosome and its product catalyzes the formation of citrulline from ornithine and carbamylphosphate in the urea cycle. About 10%–15% of patients, clinically diagnosed with OTC deficiency (OTCD), lack identifiable mutations in the coding region or splice junctions of the OTC gene on routine molecular testing. We collected DNA from such patients via retrospective review and by prospective enrollment. In nine of 38 subjects (24%), we identified a sequence variant in the OTC regulatory regions. Eight subjects had unique sequence variants in the OTC promoter and one subject had a novel sequence variant in the OTC enhancer. All sequence variants affect positions that are highly conserved in mammalian OTC genes. Functional studies revealed reduced reporter gene expression with all sequence variants. Two sequence variants caused decreased binding of the HNF4 transcription factor to its mutated binding site. Bioinformatic analyses combined with functional assays can be used to identify and authenticate pathogenic sequence variants in regulatory regions of the OTC gene, in other urea cycle disorders or other inborn errors of metabolism. We report seven disease‐causing sequence variants, six in the promoter and one in the enhancer, in patients with clinically diagnosed ornithine transcarbamylase deficiency. Functional studies revealed reduced reporter gene expression with all sequence variants. Bioinformatic analyses combined with functional assays can be used to identify and authenticate pathogenic sequence variants in regulatory regions of the ornithine transcarbamylase gene, in other urea cycle disorders or other inborn errors of metabolism.